From Calcium to NF-κB Signaling Pathways in Neurons - Lilienbaum, Alain (American Society for Microbiology, 2003)
NF-κB plays crucial roles in the nervous system, including potential roles in long-term responses to synaptic plasticity, pro- or antiapoptotic effects during developmental cell death, and neurodegenerative disorders. We report here the characterization of signaling pathways leading to the constitutive activation of NF-κB in primary cultures of neonatal cerebellar granule neurons, consecutive to calcium entry into the cytosol. We found that opening of calcium channels at the plasma membrane and at intracellular stores is indispensable for the basal NF-κB activity. We demonstrated further that three cellular sensors of the cytosolic Ca(2+) levels, calmodulin, protein kinases C (PKCs), and the p21(ras)/phosphatidylinositol 3-kinase (PI3K)/Akt pathway are simultaneously involved in the steps linking the Ca(2+) second messenger to NF-κB activity. Calmodulin triggers the activity of calcineurin, a phosphatase which plays a role in the basal NF-κB activity, while stimulation of both the calmodulin kinase II and Akt kinase pathways results in the up-regulation of the transcriptional potential of the p65 subunit of NF-κB. Finally, using pharmacological and molecular approaches, we analyze interactions between these three pathways at different levels and demonstrate a connection between PKCs and PI3K. All three components converge towards NF-κB, at the level of both nuclear translocation and transcriptional activity. These results stand in contrast to the situation in nonneuronal cells, which either do not respond to Ca(2+) or do not simultaneously activate all three cascades. By using a global approach in studying signaling pathways in neurons, these results provide further evidence to validate the concept of networks of transducing cascades, specific to cells and to physiological situations.